Migration des femmes et fécondité dans la ville de Marrakech (Maroc) - Samia R’Kha; Abdellatif Baali (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Since 1970, an increasing population  flow from the surrounging villages to the city of Marrakech, as well as to the other cities of Morocco, has been observed. The fertily of women originating from the countryside and the impact of the life in the modern city on their procreation behavior have been analysed on the basis of a sample of 1612 women living in the city of Marrakech; 22.33% are migrants. Fertility among migrants is much higher than fertility among women from the city: at the end of the reproductive period, the birth rate is of 5.37 in average for the migrants and of 3.63 for the others. Within the women who where born in the country but live in the city, fertility if influenced by the place where they spent their childhood and also by the length of time spent in the city. It became apparent that life in the modern city is responsible for changes in fertility within women populations originating from the countryside.